2017
DOI: 10.1021/acs.energyfuels.7b02095
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Management in Deadlegs: Effect of Header Temperature on Hydrate Deposition

Abstract: Deadlegs in oil and gas production systems often encounter hydrate plugs by deposition. Temperature is generally known to be an important variable in hydrate formation, but the effects in deadlegs are not exactly known. This study focuses on the effects of the header temperature on the hydrate deposition in gas-filled vertical deadlegs at constant wall temperature. All experiments are conducted with a methane/ethane gas mixture at constant pressure. The pipe wall temperature is kept constant while considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Large interfaces happen mostly in stratified, intermittent (in the elongated bodies), and free-phase flows. In cases of large interfaces where the gas is the predominant phase at the bulk (e.g., annular flow), the particles grow directly over the wall as a deposit , and a slurry flow will not be present. In smaller interfaces, the hydrates are considered to quickly encompass the entire drops/droplets.…”
Section: Topological Model For Gas Hydrate Formation Growth and Agglo...mentioning
confidence: 99%
“…Large interfaces happen mostly in stratified, intermittent (in the elongated bodies), and free-phase flows. In cases of large interfaces where the gas is the predominant phase at the bulk (e.g., annular flow), the particles grow directly over the wall as a deposit , and a slurry flow will not be present. In smaller interfaces, the hydrates are considered to quickly encompass the entire drops/droplets.…”
Section: Topological Model For Gas Hydrate Formation Growth and Agglo...mentioning
confidence: 99%
“…By using a 3 in. deadleg, Zhang et al studied the effect of header temperature on hydrate deposition in deadlegs. The experimental results showed that the header temperature has an important impact on the growth rate and distribution of the hydrate deposits, which in turn also impacted the temperature field in the deadleg.…”
Section: Introductionmentioning
confidence: 99%
“…The data in Figure 3a,b are from experiments 1−1 and 4−1, respectively. In all our studies, including our previous ones, 12,13 three types of temperature profiles have been observed: (i) when the temperature is significantly lower than the HET (e.g., by 10 °C), the temperature only slightly increases at the hydrate onset and then gradually decreases until a steady-state value (section 3 in Figure 3d); (ii) when the temperature is close to the HET, it increases initially, but then fluctuates (section 4 in Figure 3d); and (iii) when the temperature is above the HET, it increases rapidly at the beginning and reaches a steady constant value (section 5 in Figure 3d). The three patterns occur from the low to the high temperature region.…”
Section: Resultsmentioning
confidence: 68%
“…The cause of such phenomena is hydrate deposition in the pipe and has been discussed in detail in our previous papers. 12,13 Besides, the rates of the temperature change vary at different conditions. In the system with a larger ID, the change is generally slower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation